Can resistance exercise prevent breast cancer–related lymphoedema? A systematic review and metanalysis protocol - Pamela Serón; Carlos Zaror; Raúl Alberto Aguilera-Eguía; Ruvistay Gutiérrez-Arias (BMJ Open)
Introduction Evidence shows that resistance training (RT) reduces lymphoedema in patients with breast cancer–related lymphoedema (BRCL), making it a safe and efficient intervention. However, it is uncertain if RT is safe and effective in patients at risk of developing BRCL. This systematic review (SR) protocol aims to describe all methodological aspects in order to evaluate the short-, medium- and long-term effects of RT on the prevention of BCRL.Materials and methods Throughout 2024, randomised clinical trials (RCTs) will be identified in electronic databases MEDLINE/PubMed, Embase, Cochrane Central Register of Controlled Trials, PEDro and LILACS. Only studies in English, Spanish and Portuguese will be included. Grey literature and clinical trial registration will also be reviewed. The primary outcome will be the occurrence of lymphoedema and quality of life. Second, pain intensity, upper limb function, range of movement, grip strength and adverse events will be considered. The individual studies’ risk of bias will be evaluated using the Cochrane Risk of Bias 2.0 tool. Pairwise meta-analyses using a frequentist approach and random effects model will be conducted. The Grading of Recommendations Assessment, Development and Evaluation system will be used to evaluate the certainty of the evidence.Ethics and dissemination This protocol does not require the approval of an ethics committee, as it is a secondary study. The results will be disseminated through peer-reviewed publications.PROSPERO registration number CRD42023455720.